(untitled) (Research, Society and Development, 2021)
The athlete has great training demands, which intensify during the sporting seasons. Excessive training tends to overload the structures responsible for the formation of movement, the greater the overload of a structure, the greater the risk of injury and pain, amplifying the risk of withdrawing from the sport. Athletes with sports that involve repetitive throwing can cause changes in the movement of the scapula in relation to the shoulder, one of the common changes being scapular dyskinesis, which can be described as malposition of the scapula during shoulder movements or at rest. This study aims to analyze, through the scientific literature, the scapular dyskinesis index in throwing athletes. This is an integrative literature review, carried out through a survey of scientific articles that addressed the relationship between scapular dyskinesis in runners through the following databases: Pubmed, Scielo, Lilacs and Medline, published between 2016 and 2021. A search strategy totaled 90 potentially relevant articles, with the title and abstract being reviewed, only 10 articles remained, which were retained and read in full. Finally, 3 articles were considered relevant and retained for analysis. The results demonstrated that scapular dyskinesis can increase the risk for shoulder injuries in athletes. Scapular dyskinesis is commonly present in specific sports for upper limbs, and age, training volume and loads can increase the chances of upper limb injuries when compared to athletes without changes in scapular movement.